2015
DOI: 10.1109/tap.2015.2398125
|View full text |Cite
|
Sign up to set email alerts
|

Time-Domain Wideband Adaptive Beamforming for Radar Breast Imaging

Abstract: A novel wideband microwave radar imaging method is presented to detect regions of significant dielectric contrast within the breast. Clutter reduction is paramount to any radar imaging algorithm, especially with clinical patient data where the tissue composition of the breast is inhomogeneous. Time-domain Data-Adaptive imaging methods have been previously applied in a narrowband manner for microwave radar breast imaging when the received signal spectral content was wideband. In this study, a wideband time-doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 28 publications
(45 reference statements)
0
50
0
Order By: Relevance
“…The authors have previously used angles between ten and fifteen degrees as the skin contour will rarely be perfectly hemispherical and experience has shown that larger rotation angles can result in inadequate skin reflection suppression. A Peak/Mean ratio is presented to aid in comparing methodologies where the peak energy voxel is compared to the average energy within the imaged 3D space [22]. T W in is set to 0.7ns for both the compound imaging approach and the differential DAS method in each phantom experiment.…”
Section: Imaging Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The authors have previously used angles between ten and fifteen degrees as the skin contour will rarely be perfectly hemispherical and experience has shown that larger rotation angles can result in inadequate skin reflection suppression. A Peak/Mean ratio is presented to aid in comparing methodologies where the peak energy voxel is compared to the average energy within the imaged 3D space [22]. T W in is set to 0.7ns for both the compound imaging approach and the differential DAS method in each phantom experiment.…”
Section: Imaging Methodsmentioning
confidence: 99%
“…Prior to the insertion of the breast or phantom, more of the matching liquid is applied to ensure there are no air gaps present. This setup has been discussed in detail in previous studies [22], [26]. The relative permittivity and conductivity of the liquid is 9.3 and 0.22 S/m, respectively at 6 GHz and the ceramic cup has a relative permittivity of 10 and a loss tangent of 0.0005.…”
Section: A Data-acquisitionmentioning
confidence: 99%
See 2 more Smart Citations
“…BMR approaches are currently being tested in midscale clinical trials and the goal is to detect breast lesions of at least 4 mm. Although progress in image resolution and 3D imaging and faster data acquisition have been made [8][9][10], hardware design and imaging algorithm still require improvements if this technology is to be used for routine clinical use. In particular, the antenna design is important, because the antenna directs the signal to the breast to be imaged, while antennas or other sensors receive the scattered signal.…”
Section: Introductionmentioning
confidence: 99%